MUSIBAH DALAM PERSPEKTIF SUFI DAN BIL-MA'TSŪR: STUDI KOMPARATIF AL-JAILĀNĪ DAN IBN KATHĪR - Ahmad Abdullah Faqih (Makkah: Journal Of Islamic Studies, 2025)
This research examines the interpretation of Quranic verses about calamity (musibah) through a comparative analysis of two prominent Islamic scholars: Shaykh 'Abd al-Qādir al-Jailānī, representing the Sufi-ishāri approach, and Ibn Kathīr, representing the tafsīr bil-ma'tsūr tradition. Using qualitative library research methodology with a comparative (muqārin) method, this study analyzes five key verses: QS. al-Baqarah [2]:156, an-Nisā' [4]:62, asy-Syūrā [42]:30, al-Ḥadīd [57]:22, and at-Taghābun [64]:11. The findings reveal that both scholars agree calamity occurs by Allah's permission and serves as a test of faith, requiring patience and trust in God. However, significant differences emerge: al-Jailānī interprets calamity broadly, encompassing both adversity and prosperity, emphasizing spiritual education (tarbiyah ilāhiyyah) and inner consciousness, while Ibn Kathīr focuses narrowly on adversity as consequences of human sins, grounded in authentic narrations and historical context. This study concludes that both interpretive approaches complement each other, enriching Islamic scholarship and providing Muslims with comprehensive guidance for facing life's trials with proper attitudes rooted in patience (ṣabr), submission (tawakkal), and spiritual growth.